Respon Pedagang Kecil dan Masyarakat Terhadap Keberadaan Alfamart di Sei Datuk Kijang Kota Kabupaten Bintan Kepulauan Riau - Simanjuntak, Tabita Rumondang Viamaura; Rahmawati, Nanik; Syafitri, Rahma (Jurnal Ilmu Sosial dan Humaniora, 2023)
Alfamart is quite well known in big cities. Its growth is very fast, including in the Kijang city area, Sei Datuk, Kijang Kota Village is on of them. Its development is very fast within a year, it has built approximately three Alfamart outlets in Kijang City. When it was initially heard that Alfamart would be built, many had negative opinions from various parties, one of which was small traders. The limitations of a small stalls do not allow it to compete well with modern shops such as Alfamart. The rapid growth of modern shops such as Alfamart which are located close to small stalls has a negative impact on small stalls traders in terms of income which is feared to decrease after the existence of Alfamart. Intense competition occurs between small stalls and Alfamart, namely competing with each other for consumers through various activities that ultimately place consumers as the beneficiaries. The purpose of this study was to determine the community's response to the existence of Alfamart in the Sei Datuk Kijang area, Bintan City, Bintan Regency, Riau Archipelago. The approach used in this study is a qualitative approach with 9 informants and uses data collection techniques and tools in the form of observation, interviews, and documentation. The results of this study found that the response of the community and small stalls to the existence of an Alfamart in Sei Datuk Kijang city had a more positive impact. The positive impact felt was that the stimulus provided by Alfamart was very good, starting from a service perspective, a neat and clean place, making it easier to top up balances and giving discounts on certain days. Most of the small traders did not experience a decrease in income after the presence of Alfamart in Kijang City.